Descriptive analysis of the French NS-Park registry: Towards a nation-wide Parkinson's disease cohort?. (July 2019) - Mariani, Louise-Laure; Doulazmi, Mohamed; Chaigneau, Véronique; Brefel-Courbon, Christine; Carrière, Nicolas; Danaila, Teodor; Defebvre, Luc; Defer, Gilles; Dellapina, Estelle; Doé de Maindreville, Anne; Geny, Christian; Maltête, David; et al.
Abstract: Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's. The French clinical research network for PD (NS-Park) has created a national patient registry to i)report medical activity of Parkinson Expert Centers (PECs) to the Ministry of Health, ii)facilitate PD patients pre-screening for clinical trials, iii) provide a source for pharmaco-epidemiology studies. Objective: Assess the French Parkinsonian population at a nation-wide level and discover new clinical characteristics. Methods: In this feasibility study, PECs prospectively collected clinical data in a standardized manner. The population main clinical characteristics are described, focusing on motor and non-motor symptoms and treatments, assessing its representativeness. By using an unbiased clustering with multiple correspondence analysis (MCA), we also investigate potential relationships between multiple variables like symptoms and treatments, as clues for future studies. Results: Between 2012 and 2016, among 11, 157 included parkinsonian syndromes, 9454 (85%) had PD. MCA identified various profiles depending on disease duration. Occurrences of motor complications, axial signs, cognitive disorders and Levodopa use increase over time. Neurovegetative symptoms, psychiatric disorders, sleep disturbances and impulse control disorders (ICDs) seem stable over time. As expected, ICDs were associated to dopaminergic agonist use but other associations, such as ICDs and sleep disturbances for instance, or anxiety and depression, were found. Conclusions: Our results report one of the biggest PD registries ever reported and demonstrate the feasibility of implementing a nation-wide registry of PD patients in France, a potent tool for future longitudinal studies and clinical trials' population selection, and for pharmaco-epidemiology and cost-effectiveness studies. Highlights: The French clinical research NS-Park network created a national patient registry. Parkinsonian population characteristics were assessed at a nation-wide level. Relationship between multiple variables was investigated as clues for future studies. We collected data from 11, 157 parkinsonian patients, indicating the cohort feasibility. The NS-Park registry is a potent tool for clinical trials and pharmacology studies.